2019
DOI: 10.1057/s41287-019-00210-w
|View full text |Cite
|
Sign up to set email alerts
|

Living with Paradox in International Development: An Extended Case Study of an International NGO

Abstract: International Non-Governmental Organisations (NGOs) combine practical and advocacy efforts to address global challenges like poverty and climate change.However, NGOs are embedded within the same global system they seek to challenge. This article explore the tensions this raises from the vantage point of one particular organisation (Concern Universal). Drawing on a paradox perspective, we find that despite the structural constraints, NGO actors and the poor people they work alongside are active and well-informe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Gupta et al 2015;Cabral 2016;Osei-Amponsah et al 2018;Pansera and Owen 2018), their implications for innovation practises and social inclusion need to be examined. Empirical studies in Gambia has revealed that development actors, including farmers are often aware of the contradictions between various narratives and interests that guide agricultural policy and development (Wadham et al 2019). Usually, actors try to accommodate other existing narratives within their own narratives to avoid conflict (Osei-Amponsah et al 2018).…”
Section: The Hybridity Of Inclusive Innovation Narrativesmentioning
confidence: 99%
“…Gupta et al 2015;Cabral 2016;Osei-Amponsah et al 2018;Pansera and Owen 2018), their implications for innovation practises and social inclusion need to be examined. Empirical studies in Gambia has revealed that development actors, including farmers are often aware of the contradictions between various narratives and interests that guide agricultural policy and development (Wadham et al 2019). Usually, actors try to accommodate other existing narratives within their own narratives to avoid conflict (Osei-Amponsah et al 2018).…”
Section: The Hybridity Of Inclusive Innovation Narrativesmentioning
confidence: 99%
“…The Hybridity of Inclusive Innovation Narratives between Theory and Practice 73 3 social inclusion need to be examined. Empirical studies in Gambia has revealed that development actors, including farmers are often aware of the contradictions between various narratives and interests that guide agricultural policy and development (Wadham, Urquhart and Warren, 2019). Usually, actors try to accommodate other existing narratives within their own narratives to avoid conflict (Osei-Amponsah, van Paassen and .…”
Section: The Hybridity Of Inclusive Innovation Narrativesmentioning
confidence: 99%